Analisis Kebijakan Pendidikan Agama Islam dalam Menghadapi Tantangan Era Globalisasi di Madrasah - Hawwin Huda Yana; Lilik Susanti (Al-Bustan: Jurnal Pendidikan Islam, 2024)
The aim of this study is to assess how the Islamic Religious Education Policy responds to the emerging challenges in the globalized era. Qualitative methods, centered on case studies, are employed for this research. During the research process, data collection is conducted through interviews, Observation and documentation were used as methods. Afterwards, the data was analyzed using three techniques: summarizing data, presenting data, and making conclusions while ensuring the validity of the data. Islamic Religious Education encounters various challenges amidst globalization, such as moral crises, insufficiently qualified teaching staff, inadequate welfare for educators, a cognitive-centric approach to learning, suboptimal madrasah management, and negative community perceptions towards madrasahs. To address these challenges, several strategies for Islamic Education are proposed, including the development of an Islamic education paradigm, the implementation of effective educational practices, the enhancement of teaching resources' quality, and the creation of education tailored to the characteristics of the millennial generation.